An Assessment of the Role of Governmental and Non-Governmental Organisations in the Provision of Water Supply in Umunneochi and Isuikwuato Local Government Areas of Abia State, Nigeria - Umezurike, Samuel Chukwuemeka (2015)
The study assessed the role of governmental and non-governmental organizations in the provision of water supply in Abia State with a view to ascertaining their contribution in the provision of portable water and constraints therein. It further identified the various sources and quality of water supply and health related problems in Umunneochi and Isuikwuato Local Government Areas of the state.